A Community Needs Assessment Model on Heatwave-Related Health Risks in The Elderly: A Pitch - Kun Hing Yong; Cordia Chu (Journal of Accounting and Management Information Systems (JAMIS), 2023)
The pitch template initiated by Faff (2015, 2021) is employed in this pitching research letter (PRL) for my PhD research topic. It not only facilitates a systematic approach for researchers to articulate a research idea critically but also aids new PhD students and novice researchers in overcoming the uncertainties in their early research stage. This PRL comprises the introduction and brief review of the pitching template, followed by a personal reflection regarding the implementation of the framework and its benefits.
Keywords: I18; Q54; 650; Pitching Research; Community Needs Assessment Model; Heatwave; Health Risks; the Elderly